El pesado yugo del santo matrimonio: divorcio y violencia conyugal en el arzobispado de Lima (1800-1805) - Bustamante Otero, Luis (2015)
A task still pending for Peruvían historíogmphy ís tlze explomtíon of conjuga/ vio/ence. Tlze existence of some pioneering studies does not híde tlze need for more research. The present article will focus 011 tlze problem of conjuga/ ill-treatment based on tlzc mzalysis of 31 judicial cases of ecclesíastical divorce from 1800-1805. Tlze m·ticle specífically tries to examine the nature of some marital relations, starting witlz tlze premise that these developcd within a patriarc/zal society. Besides, an attempt is made to slww lww tlzis society was framed by a conjuncture of lzeiglztened marital conflicts. Final/y, conjuga/ víolence is examined on tlze one lzmzd as tlze main factor for sepamtion ("divorce"), but also as a consequence or effect of far deeper motives. Last of all, ma/e defensíve reactíons are likewise noted.